2019
DOI: 10.1038/s41467-019-09669-x
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature ferroelectricity in MoTe2 down to the atomic monolayer limit

Abstract: Ferroelectrics allow for a wide range of intriguing applications. However, maintaining ferroelectricity has been hampered by intrinsic depolarization effects. Here, by combining first-principles calculations and experimental studies, we report on the discovery of robust room-temperature out-of-plane ferroelectricity which is realized in the thinnest monolayer MoTe 2 with unexploited distorted 1T ( d 1T) phase. The origin of the ferroelectricity in d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
357
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 394 publications
(364 citation statements)
references
References 33 publications
5
357
1
1
Order By: Relevance
“…In 2019, Yuan et al reported an experimental observation of room temperature ferroelectricity in monolayer d1T-MoTe 2 . [120] They used X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy to confirm the elemental composition and compare the phase differences, as shown in Figure 11a. Then, the atomic structure differences in the 2H and d1T phases were illustrated by high-resolution transmission electron microscopy (HRTEM), where some Te vacancies were observed in the d1T phase (Figure 11b,c).…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Yuan et al reported an experimental observation of room temperature ferroelectricity in monolayer d1T-MoTe 2 . [120] They used X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy to confirm the elemental composition and compare the phase differences, as shown in Figure 11a. Then, the atomic structure differences in the 2H and d1T phases were illustrated by high-resolution transmission electron microscopy (HRTEM), where some Te vacancies were observed in the d1T phase (Figure 11b,c).…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…Except for employing van der Waals ferroelectric materials, exploring IP ferroelectricity in compounds is also a good choice for obtaining nanoscale Reproduced with permission. [120] Copyright 2019, Nature Publishing Group. www.advelectronicmat.de ferroelectrics.…”
Section: Bis(benzylammonium) Lead Tetrachloridementioning
confidence: 99%
“…Compared to other reported double layered MXenes, Nb 2 C possesses an excellent conductivity with almost zero or small bandgap that also furnishes its prominence which is distinct from traditional 2D materials. [ 10,19,20 ] In the merit of good biocompatibility, near‐infrared (NIR) adsorption, and high photothermal conversion performance, [ 21 ] Nb 2 C is chosen as a promising candidate for both in vitro and in vivo photothermal/bio‐detection applications. [ 6,7 ] On the other hand, Nb 2 C, which exhibits a good ion intake ability, is vastly used as a cathode for metal ion battery.…”
Section: Figurementioning
confidence: 99%
“…1b) is a Weyl semi-metal in the bulk form. Since the discovery of topological superconductivity and large magnetoresistance in this compound it has been the subject of comprehensive fundamental research [11][12][13][14] . In addition, 1T′-MoTe 2 has been highlighted as an emerging energy material with applications ranging from photovoltaic cells to hydrogen evolution catalysis [15][16][17] .…”
mentioning
confidence: 99%